Families torsion and morse functions - Bismut Jean-Michel; Goette Sebastian (Paris Societe Mathematique de France, 2001)
This paper represents a formula for the analytic torsion forms in the Rham theory introduced by Bismut and Lott [Blo1]. The techniques used in this paper are Superconnections and Chern-Simons theory, an extended the Rham map, the Witten complex and the i
Keywords: Analytic torsion forms; de Rham theory; Vector bundles